Probing the Influence of Acidity and Temperature to Th(IV) on Hydrolysis, Nucleation, and Structural Topology - Lin, Jian; Qie, Meiying; Zhang, Linjuan; Wang, Xiaomei; Lin, Yuejian; Liu, Wei; Bao, Hongliang; Wang, Jianqiang (Inorganic chemistry, 2017)
Systematic control of the molar ratio between thorium hydroxides and selenic acid and their reaction temperature under hydrothermal conditions results in four novel thorium-based selenate complexes, namely, [Th8O4(OH)8(SeO4)6(H2O)16]·(SeO4)2·13H2O (Th-1), [Th8O4(OH)8(SeO4)8(H2O)13]·7H2O (Th-2), Th(OH)2(SeO4)H2O (Th-3), and Th3(SeO4)6(H2O)6·2.5H2O (Th-4), as well as the thorium mixed selenite selenate compound Th(SeO3)(SeO4) (Th-5). Smaller [H2SeO4]/[Th(IV)] ratio or lower temperature give rise to the formation of octameric [Th8(μ3-O)4(μ2-OH)8]16+ cores in Th-1/Th-2 and infinite [Th(μ2-OH)2H2O]2+ chains in Th-3, respectively. Increasing the [H2SeO4]/[Th(IV)] ratio or elevating the temperature generates a microporous (11.3 Å voids) open-framework Th-4, a monomeric thorium species without oxo/hydroxyl ligands, and a three-dimensional thorium structure Th-5. Formation of these compounds suggests that variables including acidity and temperature play a critical role in the hydrolysis and oligomerization of ThIV ions. Increasing acidity limits the deprotonation of water molecules and formation of nucleophilic hydroxo/oxo-aquo Th species, and high temperature appears to suppress the olation/oxolation hydrolysis reactions, which in both ways limit the formation of the thorium oligomers.